2019
DOI: 10.1037/men0000196
|View full text |Cite
|
Sign up to set email alerts
|

Masculine gender role expectations in China: A consensual qualitative research-modified study.

Abstract: Much of the psychological literature is either focused on non-Hispanic White heteronormative forms of masculinities or utilizes measures that were developed primarily with White middle-class heterosexual men in the United States. This qualitative study sought to understand masculine gender role expectations in mainland China. A total of 50 men and 75 women were recruited to participate in this study through Sina Weibo. Responses were analyzed using consensual qualitative research–modified (Spangler, Liu, & Hil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Second, the main assumptions of the universality of this application of RCT need to be examined. Differences in emphasis and expression of emotion and/or masculinity have been noted based on culture of origin (e.g., Arciniega et al, 2008; Lease et al, 2013; Matsumoto et al, 2008, Song & Liang, 2019; Yeung et al, 2015) and are, as noted by Di Bianca and Mahalik (2022), influenced by racism in the United States (U.S.; e.g., Powell et al, 2016). However, a foregrounding of the intersections in their applications is needed.…”
Section: Deepening the Rct Approachmentioning
confidence: 99%
“…Second, the main assumptions of the universality of this application of RCT need to be examined. Differences in emphasis and expression of emotion and/or masculinity have been noted based on culture of origin (e.g., Arciniega et al, 2008; Lease et al, 2013; Matsumoto et al, 2008, Song & Liang, 2019; Yeung et al, 2015) and are, as noted by Di Bianca and Mahalik (2022), influenced by racism in the United States (U.S.; e.g., Powell et al, 2016). However, a foregrounding of the intersections in their applications is needed.…”
Section: Deepening the Rct Approachmentioning
confidence: 99%
“…To illustrate, eight of the 10 most prevalent subjective masculine norms in our study that met the 10% threshold were also present among the most prevalent subjective masculine norms in Singapore that met a similar 10% threshold—emotional toughness, providing for family, avoidance of femininity, being a gentleman, work, nonaggression, avoidance of homemaking, and physicality. Relatedly, a recent qualitative study on masculine gender role expectations in China also identified a somewhat similar set of perceived masculine norms—responsible, honest and law-abiding, caring, brave and self-starting, forgiving, respectful and nonviolent, rational and calm, and avoid femininity (Song & Liang, 2019). Tentatively, these findings might suggest the presence of a core set of contemporary transcultural masculine norms in multiple (although not necessarily all) cultures.…”
Section: Discussionmentioning
confidence: 93%
“…Accordingly, subjective masculine norms are defined as people’s perceptions of the most important masculine norms in a society or group. To identify the most prevalent subjective masculine norms, Wong and colleagues (2016) advocated a bottom-up approach—instead of using a predetermined set of masculine norms identified by researchers, they posed open-ended questions about participants’ perceptions of the most important injunctive masculine norms; the researchers then coded their qualitative responses and computed their frequencies to determine the most prevalent masculine norms (also, see Song & Liang, 2019). Using this approach, Wong and colleagues (2016) found that providing for family, being a gentleman, emotional toughness, avoidance of inferiority to women, and avoidance of femininity were the five most prevalent subjective masculine norms in Singapore in a sample of 348 Singaporean university students.…”
Section: Subjective Gender Norms Modelmentioning
confidence: 99%
“…The themes we identified in Asian American men’s masculinity ideology overlap with Chinese nationals’ descriptions of their masculine gender role expectations (Song & Liang, 2019). Specifically, of the eight “domains” identified, being responsible, caring, respectful and nonviolent, and rational overlapped with our findings of Asian American men’s reports of real men being responsible, taking care of others, being respectful, never harming women, and being cognitively disciplined.…”
Section: Discussionmentioning
confidence: 94%